S100a4 promotes metastatic transformation in non-metastatic liver cancer cells through NMIIa binding: mechanistic insights - Yong Qin; Chaojun Wang; Shengqian Xu; Junbin Zhou; Shimiao Li; Hailin Ye (BMC Cancer)
Abstract Background Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, characterized by high recurrence and metastasis rates. Studies have demonstrated that exosomes, as signaling mediators between tumor cells and their microenvironment, play crucial roles in tumor cell migration and invasion. S100A4, a known metastasis-associated protein, has been identified as a key factor in promoting cancer cell migration and epithelial-mesenchymal transition (EMT). Methods To investigate the relationship between S100A4 and high metastasis in HCC, we performed analyses using TCGA-HCC data and clinical samples. Stable HCC cell lines overexpressing S100A4 were established to evaluate S100A4 expression levels among various HCC cell types. The migration and invasion capabilities of these cells were assessed using wound healing and Transwell assays. Additionally, Western blotting, qPCR, and immunohistochemistry (IHC) were employed to detect changes in EMT-related markers and NMIIA expression following S100A4 overexpression. Results Data from TCGA and IHC analyses revealed that S100A4 is highly expressed in HCC patients and that its elevated expression correlates with lymph node metastasis and advanced tumor stage. High S100A4-expressing (S100A4^H) HCC cells (JHH-1 and Li-7) exhibited enhanced migratory and invasive capabilities, whereas low S100A4-expressing cells (Huh-7 and Hep G2) displayed weaker metastatic characteristics. Exosomes derived from S100A4^H cells also showed elevated levels of S100A4. Overexpression of S100A4 in HCC cells promoted cell migration, invasion, and viability. Moreover, exosomes derived from S100A4^H cells significantly enhanced the migration and invasion of co-cultured HCC cells. Mechanistically, S100A4 overexpression significantly downregulated E-cadherin expression while upregulating Twist1, N-cadherin, and Vimentin levels. Notably, S100A4 formed a complex with NMIIA in HCC cells, and NMIIA silencing suppressed S100A4-induced changes in EMT-related protein expression. Conclusion S100A4 promotes HCC cell migration, invasion, and metastasis by activating the EMT process via NMIIA, potentially through exosome-mediated signaling. S100A4 may serve as a potential biomarker for predicting EMT occurrence, disease progression, and prognosis in HCC patients.